Effects of clinical stage, behavioral and psychological symptoms of dementia, and living arrangement on social distance towards people with dementia - Kae Ito; Shuji Tsuda (PLoS ONE, 2025)
Background Dementia presents significant challenges, including social exclusion, which can be exacerbated by public stigma. This study aimed to clarify how social distances, a common measure of public stigma, towards people living with dementia and its associated factors vary with clinical stage, presence of behavioral and psychological symptoms of dementia (BPSD), and living arrangements. Methods The study involved 2,589 Japanese participants aged 40 to 90 years. They were exposed to one of four vignettes depicting an 80-year-old woman progressing from normal ageing to mild, moderate, and severe dementia: Vignette A (living with husband, without BPSD); Vignette B (living with husband, with BPSD); Vignette C (living alone, without BPSD); and Vignette D (living alone, with BPSD). Results Social distance showed no significant differences in the normal aging and mild stage of dementia across all vignettes. At the moderate stage, social distance was higher for individuals exhibiting BPSD, regardless of living arrangement. At the severe stage, the lowest social distance was observed towards individuals living with their family without BPSD, whereas the highest was towards those living alone, exhibiting BPSD. For Vignette A, possession of social capital (p<0.001) and having experience of social contact with people living with dementia (PLWD) (p = 0.001–0.007) were independently associated with lower social distance across all dementia stages. In addition, in the mild stage of dementia, high perceived social support (p = 0.005) and having knowledge about dementia (p = 0.036) were associated with lower social distance, but not in the moderate or severe stage of dementia. For Vignette D, possession of social capital (p≤0.001) and having experience of social contact with PLWD (p<0.001 to p = 0.006) were independently associated with lower social distance across all dementia stages. In mild dementia, female sex (p = 0.004) and knowledge about dementia (p = 0.026) were associated with lower social distance. Furthermore, in mild and moderate dementia, living in rural area (p = 0.003–0.048) was associated with lower social distance. Conclusions Social distance is higher toward PLWD who live alone and exhibit BPSD than toward those who live with family and/or do not show BPSD, indicating a higher risk of exclusion for the former. Moreover, factors affecting social distance towards PLWD vary across different clinical stages of dementia. While greater knowledge about dementia is associated with lower social distance toward PLWD, this effect appears to be most pronounced in the mild stage. In contrast, opportunities for social contact with PLWD are crucial for achieving lower social distance across all stages of dementia. The findings underscore the need for stage-specific interventions to address stigma, with a focus on education and opportunities for social contact. Targeted efforts are especially important for promoting the inclusion of PLWD who live alone and exhibit BPSD.